2019
DOI: 10.1111/jfpp.14171
|View full text |Cite
|
Sign up to set email alerts
|

Processing, storage, and quality characteristics of wheat‐based snack

Abstract: Gluten proteins in wheat bring about the viscoelastic properties when water is mixed with the flour to form a dough. Processing of whole‐wheat flour by moist heat reduced the viscoelastic properties in the dough. The baked savory snack prepared from processed whole‐wheat flour simulates the fried snack. Snacks prepared by sheeting, cutting, and baking were evaluated for spread ratio, breaking strength, color, and sensory characteristics. Snack from processed flour had crisp texture (1,300 g force) compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 25 publications
1
11
3
Order By: Relevance
“…Tiwari et al (2011) stored deep‐fried snacks formulated with rice and legume flours for 30 days at 29°C, packaged in polypropylene pouches, and observed moisture gains ranging from 1.72% to 1.84%. The moisture of WBFSs was higher at the end of our study; however, the levels were similar to previous studies reported by Chandrashekhar et al (2019) and Tiwari et al (2011). As shown in Figure 1, Pilosof’s model accurately fitted the experimental moisture increments during storage at the studied temperatures.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Tiwari et al (2011) stored deep‐fried snacks formulated with rice and legume flours for 30 days at 29°C, packaged in polypropylene pouches, and observed moisture gains ranging from 1.72% to 1.84%. The moisture of WBFSs was higher at the end of our study; however, the levels were similar to previous studies reported by Chandrashekhar et al (2019) and Tiwari et al (2011). As shown in Figure 1, Pilosof’s model accurately fitted the experimental moisture increments during storage at the studied temperatures.…”
Section: Resultssupporting
confidence: 92%
“…Moisture was higher than that (1.4%) reported by Chandrashekhar et al (2019) for wheat-based snacks containing oil (WBSCO). Chandrashekhar et al (2019) reported lower fat content (16%) for their WBSCO.…”
Section: Wbfs Properties and Sensory Analysiscontrasting
confidence: 59%
See 3 more Smart Citations